Oral health and vitamin D in adult: a systematic review - Normaliza Ab Malik; Saari Mohamad Yatim; Kasmawati Norhidayati Mokhtar; Waruna Lakmal Dissanayaka; George Pelekos; Colman McGrath; Siti Nur Rasyidah Md Ramli (Cambridge University Press, 2024)
Indexed by WOS/SCOPUS/ERA